JUNGLE RUBBER AND PIONEER TREE: INVESTIGATING LEAF MORPHOLOGICAL VARIATION OF Alstonia scholaris R. BR. IN JAMBI - Inggar Damayanti (Jurnal Belantara, 2023)
Human activity has reduced natural forests in Indonesia and triggered their transformation into, for example, jungle rubber land, as is often found in the Jambi Province of Central Sumatera. Forming jungle rubber through successional processes involves important pioneer trees such as Alstonia scholaris. The pioneer species' performance is influenced by site factors, the initial biodiversity status, cultivation treatment, and management inputs. The study reported here was conducted to assess leaf morphological variation of A. scholaris as preliminary indicators of difference in response and growth performance in several CRC990 plots (50 m x 50 m) of two distinct landscapes: Bukit Dua Belas National Park and Harapan Rain Forest. Results of the analysis of variance showed that the difference in landscapes gave rise to a significant effect on leaf morphology variable NV (venation number) for A. scholaris. Differences between plots within the landscapes were significant in the variables venation number (NV) and petiole ratio (PR) for A. Scholaris. The results of the distribution of leaf morphological variation in A. scholaris based on multivariate analyses (PCA) showed no clustering due to landscape effects.